Posted by Jetta on Wednesday, August 4, 2010 at 9:46am.
are they correct?
4. (2X-3)/(4X-1) -Div by (6X^2-13X+6)/
(15X^2-7X-2).
Factor trinomial in numerator using A*C Method:
A*C = 6*6 = 36 = -4*-9,
6X^2 -4X-9X +6
Group the 4 terms in pairs and factor each pair:
2X(3X-2) -3(3X-2). Factor out (3x-2):
(3X-2) (2X-3).
Factor the trinomial in denominator
using A*C Method:
A*C = 15*-2 =-30 = 3*-10.
15X^2 +3X-10X -2.
Group the 4 terms in pairs and factor each pair:
3x(SX+1) -3(5X+1), Factor out (5x+1):
(5X+1) (3X-2).
Write original expression in factored form:
(2X-3)/(5X+1) Div by (3X-2)(2X-3)/
(5X+1)(3X-2).
Cancel the (3X-2) factors:
(2X-3)/5X+1) Div by (2X-3)/(5X+1).
Invert divisor and multiply:
(2X-3)/(5X+1) * (5X+1)/(2X-3).
Cancel the (5X+1) factors:
(2X-3)/(2X-3) = 1.
5. (X^3-9)/(X^2+11X+24) * (X^2+7X-8_/
(X^2-4X+3) =
Factor both numerators & denominators:
X(X^2-9)/(X+3)(X+8) * (X-1)(X+8)/
(X-1)(X-3) =
Cancel factors (X+8), and (X-1).
X(X^2-9)/(X+3) * 1/(X-3)
Factor (X^2-9):
X(X+3)(X-3)/(X+3) * 1/(X-3).
Cancel factors (x+3) & (X-3):
= X.
6.(4X -8)/(X^2 -X -6) Div (X^3+X^26X)/
(X^2-9)
Factor completely:
4(X-2)/(X-3)(X+2) Div X(X^2+X-6)/(X+3)
(X-3).
4(X-2)/(X-3)(X+2) Div X(X+3)(X-2)/(X+3)(X-3).
Cancel factor (X+3) and invert divisor
4(X-2)/(X-3)(X+2) * (X-3)/X(X-2).
Cancel factors (X-2), (Z-3)
4/X(X+2).